The Small and Dynamic Pre-primed Pool at the Release Site; A Useful Concept to Understand Release Probability and Short-Term Synaptic Plasticity? - Gustafsson, Bengt; Ma, Rong; Hanse, Eric (Frontiers in Synaptic Neuroscience, 2019)
Advanced imaging techniques have revealed that synapses contain nanomodules in which pre- and post-synaptic molecules are brought together to form an integrated subsynaptic component for vesicle release and transmitter reception. Based on data from an electrophysiological study of release from synapses containing a single nanomodule and data from such imaging studies, we present a possible modus operandi of such a nanomodule. We suggest that a nanomodule, despite containing a number of release locations, operates as a single release site, releasing at most a single vesicle at a time. The nanomodule is equipped with two separate sets of release locations, one set that is responsible for release only at the onset of synaptic activity and another set that produces the release thereafter. At the first set of release locations vesicles are primed by synaptic inactivity lasting seconds, this synaptic inactivity also resulting in a dispersal of values for vesicle release probability among the synapses. Following a single presynaptic action potential, this dispersal is reversed in a release-independent manner, and the release produced from the second set of release locations, by vesicles rapidly primed after onset of synaptic activity, is more equal among the synapses. This normalization of vesicle release probability after onset of synaptic activity is instrumental in producing the heterogeneity in facilitation/depression behaviour among the synapses, and can be seen as a means to create differential dynamics within a synapse population.